DEVELOPMENTS AND EMERGING ISSUES IN PUBLIC AND PRIVATE HEALTH CARE SYSTEMS OF KERALA - LEKSHMI S; G.P.MOHANTA; K.G.REVIKUMAR; P.K.MANNA (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Kerala was universally recognized for its good health indicators. Even before independence the specific policies, efforts and expenditure for health by the Maharajas of Travancore and Cochin was remarkable. The unswerving governmental support for the welfare sectors till the mid 1980s served as a catalyst for the development of health services in Kerala. This was also reflected in the expansion of health infrastructure. During the periods between 1960s to mid 1980s there was an increase in the public sector institutions. But thereafter the pace of growth of public health care system slowed this decline was made good by the private medical care setup which makes Kerala one of the state with the highest reductions in public health sector contributions.